Longitudinal affective response to high-intensity interval training and moderate-intensity continuous training in overweight women with polycystic ovary syndrome: A randomised trial. (January 2023) - Patten, Rhiannon K.; Bourke, Matthew; McIlvenna, Luke C.; Moreno-Asso, Alba; Woessner, Mary N.; Stepto, Nigel K.; Parker, Alexandra
Abstract: Background: Women with polycystic ovary syndrome (PCOS) experience general and PCOS-specific barriers that limit their engagement with exercise and contribute to high attrition from exercise programs, hindering the potential benefits of exercise to address their increased cardio-metabolic risk. A positive remembered affective response can predict future intentions and adherence to exercise prescription. Objectives: To compare the longitudinal changes in remembered affect to high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) in women with PCOS and to determine whether longitudinal changes in remembered affect are correlated with changes in fitness, body mass index, adherence and exercise enjoyment. Methods: Physically inactive, overweight women with PCOS were randomly assigned to 12 weeks of either HIIT (n = 15) or MICT (n = 14) (3 sessions per week). Remembered affective valence (Feeling Scale) was collected after each exercise session. Cardiorespiratory fitness (VO2peak ) was assessed at baseline and post-intervention. Exercise enjoyment was assessed post-intervention. Results: The longitudinal changes in the remembered affect were more positive in the HIIT group compared to MICT (β = 0.017, p = 0.047). HIIT was also considered more enjoyable than MICT (p = 0.002). Adherence was high in both groups (>90%). We found a moderate correlation with longitudinal changes between the remembered affect and change in fitness (rs = 0.398) and exercise enjoyment (rs = 0.376) using the combined group, however, these were not statistically significant (p = 0.054 and p = 0.064, respectively). Conclusions: HIIT demonstrated a more positive longitudinal remembered affective response and greater exercise enjoyment compared to MICT in overweight women with PCOS. Highlights: Women with polycystic ovary syndrome (PCOS) report barriers to exercise. High-intensity interval training (HIIT) had a positive affective response over time. HIIT was more enjoyable than moderate-intensity continuous training (MICT). Adherence to both HIIT and MICT was high in women with PCOS. HIIT is a promising exercise intervention for overweight women with PCOS.